The concept of development of computer aided design programs for bridges or other engineering structures according to the specified criterion of optimality - Pavel M. Salamakhin (Structural Mechanics of Engineering Constructions and Buildings, 2019)
In article on the basis of generalization of experience of creating in the period from 1997 to 2015 computer-aided design of various bridge structures by fifteen graduate students of the Department of Bridges and Transport Tunnels MADI (GTU) under the leadership of Doctor of Technical Sciences, Professor P.M. Salamakhin the authors proposed the concept of the development of the structure of standard programs of computer-aided design of bridge or other engineering structures according to the given optimality criterion. Given in the most general form of the complete block diagram of such programs with the detailed disclosure of the indicator of simultaneous execution of a set of requirements in all elements of the structure dependent scale in the sequential approach the minimum possible values, and also demonstrates how to determine the combination of values of all independent parameters of structures that provide the design of facilities according to the given optimality criterion. When working on the article, some provisions of earlier studies and the state of development of automation of design of bridge structures abroad are taken into account. The authors proceed from the fact that the proposed concept of development of computer-aided design of bridge and other engineering structures according to the specified criterion of optimality can and should be used as a model in the development of computer-aided design of structures with various generalized design schemes.